2015
DOI: 10.2169/internalmedicine.54.2797
|View full text |Cite
|
Sign up to set email alerts
|

Associations SELE Gene Haplotype Variant and Hypertension in Mongolian and Han Populations

Abstract: Genetic variation is thought to contribute to the etiology of hypertension, and E-selectin is a candidate essential hypertension-associated gene. Objective In this study, we attempted to test the hypothesis that subtle haplotype variants of SELE genes may be sources of essential hypertension in Mongolian and Han populations. Materials A total of 429 unrelated Mongolian herdsmen and 416 Han farmers were enrolled, including 212 Mongolian essential hypertension (EH) patients, 217 Mongolian normotensives (controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(17 reference statements)
0
3
0
1
Order By: Relevance
“…The results for myopia and hyperopia were compared with those of emmetropic individuals myopia, whereas Mongolian ethnicity was a risk factor for hyperopia. Apart from indicators included in our study, differences between Han and Mongolian populations have also been found in their genetic background [10,[15][16][17]31], diet [18], alcohol consumption [32], sleeping habits [33,34], body structure [35,36] and morphological traits [37]. The differences in the prevalence of and risk factors for RE in the Han and Mongolian populations could not be explained by the differences in the risk factors investigated in this study.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The results for myopia and hyperopia were compared with those of emmetropic individuals myopia, whereas Mongolian ethnicity was a risk factor for hyperopia. Apart from indicators included in our study, differences between Han and Mongolian populations have also been found in their genetic background [10,[15][16][17]31], diet [18], alcohol consumption [32], sleeping habits [33,34], body structure [35,36] and morphological traits [37]. The differences in the prevalence of and risk factors for RE in the Han and Mongolian populations could not be explained by the differences in the risk factors investigated in this study.…”
Section: Discussionmentioning
confidence: 62%
“…Other studies have suggested that in the Mongolian population, the risk of cardiovascular diseases is higher than in the Han population [12,13], but the risk of stroke is lower [14]. Moreover, there is some evidence suggesting that the difference in the risk of diseases might be based on the genetic heterogeneity [15][16][17] and different lifestyles such as dietary habits [18] between the Han and Mongolian populations.…”
Section: Introductionmentioning
confidence: 99%
“…Third, genetic factors are another important factor associated with hypertension in China. Many related studies had been performed in China and the results showed that human cytochrome P450 had the most important influence on the development of essential hypertension in China 17 19 . However, no consideration was given to this factor in this study because of the lack of genetic information.…”
Section: Discussionmentioning
confidence: 99%
“…으로 알려져 있는데 [7][8][9], 그 중에서 MACROD2 (MACRO domain containing 2) 유전자가 심혈관 질환 및 고혈압과 상관 관계가 있는 것으로 발표되었다 [10][11][12][13]. MACROD2는 mono-ADP-ribosylated 된 단백질로부터 ADP-ribose를 제거하는 데 관여하는 탈아세틸화효소의 기능을 가지고 있는데, DNA 손 상 시 핵에서 세포질로 전위하는 것으로 나타났으며, 이는 태아 와 성인의 뇌, 흉선, 골격근, 간, 췌장, 전립선, 신장, 폐에서 발현 하며 쥐 배아와 성체의 in situ hybridization과 RT-PCR분석에 서 배아일 12.5일에서 성년기까지 두뇌, 특히 심실영역에서의 발현을 나타냈다 [14].…”
unclassified